Imprint Desorption Electrospray Ionization Mass Spectrometry Imaging (IDESI-MSI) Reveals Absorption of Triclopyr-Based Herbicide in Plants and Mouse Organs - Hanzhi Liu; Yunshuo Tian; Ruolun Wei; Yifan Meng; Richard N. Zare (Metabolites, 2025)
Background: Understanding the absorption and distribution of herbicides in plants and animal tissues is essential for assessing their potential risks to human health. Method: In this study, we employed imprint desorption electrospray ionization mass spectrometry imaging (IDESI-MSI) to visualize in both vegetable and animal tissues the absorption of Roundup which is a widely used herbicide. Results: Using IDESI-MSI with a pixel size of 150 µm, we detected the herbicide alongside several endogenous metabolites on oil-absorbing films applied to carrot sections. Time-course experiments revealed progressive herbicide penetration into carrot tissue, with penetration depth increasing linearly over time at a rate of approximately 0.25 mm/h. In contrast, green pepper samples showed minimal herbicide infiltration, likely owing to their hydrophobic cuticle barrier. Additionally, mice fed with herbicide-treated carrots exhibited detectable levels of herbicide in liver and kidney tissues. Conclusions: These findings highlight the utility of IDESI-MSI as a powerful analytical platform for the rapid evaluation of chemical migration and absorption in food and biological systems, with important implications for food safety and toxicological research.